Hybrid machining: A review on recent progress - Nurul Nadia, Nor Hamran; J. A., Ghani; R., Ramli; W. M. F., Wan Mahmood (Springer, 2024)
Hybrid manufacturing, a pioneering concept in modern industry, combines various manufacturing methods to achieve unparalleled performance and versatility. By seamlessly integrating diverse technologies, it overcomes limitations of individual techniques while leveraging their strengths. This review explores recent progress in hybrid manufacturing, including trends, performance outcomes, and challenges. Notably, there is a substantial trend towards combining traditional and additive manufacturing (59%). Processes like WAAM, LMD, SLM, FFF, and FDM gain traction, especially for materials like ferrous metals, non-ferrous metals, and composites. Performance outcomes are substantial. WAAM improves part performance, geometry control, efficiency, surface quality, and environmental impact. LMD integration enhances feature addition, stability, precision, and resource efficiency. SLM combined with subtractive methods enhances surface quality, mechanical properties, and intricate part feasibility. FFF combined with subtractive techniques addresses anisotropy, surface roughness, and geometric accuracy. Laser-assisted methods like LOMM and LAM enhance material removal, surface quality, and machining efficiency. Vibration-assisted techniques boost material removal rate, surface quality, and overall machining performance. However, challenges in hybrid machining are evident across multiple categories, including workpiece materials, machine tool development, process understanding, monitoring systems, heat affected zones, equipment costs, productivity, environmental impact, qualification procedures, and technology transfer. Overcoming these challenges requires interdisciplinary collaboration, innovative solutions, and technological advancements. Effectively addressed, hybrid machining has the potential to revolutionize manufacturing, significantly improving efficiency, precision, and sustainability.